Blue Light Damage and p53: Unravelling the Role of p53 in Oxidative-Stress-Induced Retinal Apoptosis - Agnes Fietz; Francesca Corsi; José Hurst; Sven Schnichels (MDPI AG, 2023)
In the digital age, the widespread presence of electronic devices has exposed humans to an exceptional amount of blue light (BL) emitted from screens, LEDs, and other sources. Studies have shown that prolonged exposure to BL could have harmful effects on the visual system and circadian rhythm regulation. BL is known to induce oxidative stress, leading to DNA damage. Emerging research indicates that BL may also induce cell death pathways that involve the tumor-suppressor protein p53. Activated p53 acts as a transcription factor to regulate the expression of genes involved in cell cycle arrest, DNA repair, and apoptosis. This study aimed to explore the implication of p53 in BL-caused retinal damage, shedding light on the potential mechanisms of oxidative-stress-induced retinal diseases. BL-exposed porcine retinal cultures demonstrated increased p53- and caspase-mediated apoptosis, depending on exposure duration. Direct inhibition of p53 via pifithrin α resulted in the prevention of retinal cell death. These findings raise concerns about the long-term consequences of the current daily BL exposure and its potential involvement in various pathological conditions, including oxidative-stress-based retinal diseases like age-related macular degeneration. In addition, this study paves the way for the development of novel therapeutic approaches for oxidative-stress-based retinal diseases.